University funding systems: impact on research and teaching - John Beath; Joanna Poyago-Theotoky; David Ulph (Kiel Institute for the World Economy (IfW), 2011)
We address the following question: how does a higher education funding system influence the trade-off that universities make between research and teaching? We do so by constructing a model that allows universities to choose actively the quality of their teaching and research when faced with different funding systems. In particular, we derive the feasible sets that face universities under such systems and show how, as the parameters of the system are varied, the nature of the university system itself changes. The culture of the university system thus becomes endogenous. This makes the model useful for the analysis of reforms in funding and also for international comparisons.
Keywords: I21; I22; I23; 330; university funding systems; higher education; research quality; teaching quality; university budget constraint